Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$f(x)=x^3-6x^2+9x-5$ is given.

What is the value of $$\lim_{h\to0}\frac{[f'(1+2h)+f'(3-3h)]}{2h}$$

I tried to use the definition of derivative,and here it seems like the expression will be equal to something like the 2nd derivative of $f(x)$ but I'm confused with $2h$ and $-3h$.

share|improve this question
    
The answer is given as -15. –  guest Aug 22 '13 at 0:13
1  
you mean confuse*d* :) –  nbubis Aug 22 '13 at 0:14
    
Thanks :) It should be mathandgrammer.stackexchange :) –  guest Aug 22 '13 at 0:15
    
Do you know l'Hopital's rule? –  Ataraxia Aug 22 '13 at 0:19
    
Yes but I use it when the limit results in 0/0 or inf/inf. Can we use it for this question? –  guest Aug 22 '13 at 0:21

4 Answers 4

up vote 1 down vote accepted

Hint: Note that $f'(1)=f'(3)=0$. Rewrite our limit as $$\lim_{h\to 0} \frac{f'(1+2h)-f'(1)}{2h}+\lim_{h\to 0}\left(-\frac{3}{2}\right)\frac{f'(3-3h)-f'(3)}{-3h}.$$

share|improve this answer
    
I was looking for such an answer but I didnt see that f'(1)=f'(3)=0. I added -f'(1)+f'(1) [ and the same for f'(3) ] so they made the expression a bit complicated for me.Thank you –  guest Aug 22 '13 at 0:36

We have $$f'(x)=3x^2-12x+9$$ and notice that $$f'(1)=f'(3)=0$$ Now by the definition of the derivative we have $$\lim_{h\to0}\frac{[f'(1+2h)+f'(3-3h)]}{2h}=\lim_{u\to0}\frac{f'(1+u)-f'(1)}{u}-\frac{3}{2}\lim_{v\to0}\frac{f'(3+v)-f'(3)}{v}\\ =f''(1)-\frac{3}{2}f''(3)=-15 $$

share|improve this answer
    
I think this question is asked so that I should play with h values and end up with second derivative like in your solution. Thank you. –  guest Aug 22 '13 at 0:46
    
You're welcome. –  Sami Ben Romdhane Aug 22 '13 at 0:50

Hints:

  • $f'(1+ 2 h) = 9 - 12 (1 + 2 h) + 3 (1 + 2 h)^2$
  • $f'(3-3h) =9-12 (3-3 h)+3 (3-3 h)^2$
  • $f'(1+2h) + f'(3-3h) = 8-12 (3-3 h)+3 (3-3 h)^2-12 (1+2 h)+3 (1+2 h)^2$

So, we have:

$$\lim_{h\to0}\frac{[f'(1+2h)+f'(3-3h)]}{2h} = \lim_{h\to0}\dfrac{-30 h + 39 h^2}{2h} = \lim_{h\to0}\dfrac{-30 + 39 h}{2} = -15$$ Can you fill in the details?

share|improve this answer
    
$\quad + 1 \quad$ –  amWhy Aug 22 '13 at 0:27
    
@amWhy: Thanks! Hope you are having a beautiful day! :-) –  Amzoti Aug 22 '13 at 0:27
    
You filled all the details in,thanks :) –  guest Aug 22 '13 at 0:41
    
@guest: You are very welcome! Regards –  Amzoti Aug 22 '13 at 0:42
    
Let's get you $\geq 20$K by week's end!! –  amWhy Aug 22 '13 at 12:35

This is not the second derivative, since the points the first derivative is evaluated at are not the same points. That being said, you can just calculate the first derivative, plug in $1+2h, 3-3h$, and see what you get.

For reference, note that you'll get (after some simplification): $$\lim_{h\to 0} \frac{3h(13h-10)}{2h}=\lim_{h\to 0} \frac{-30h}{2h}=-15$$

share|improve this answer
    
Thanks but I thought that there is a way by playing h values instead of plugging in 1+2h and 3-3h. –  guest Aug 22 '13 at 0:30

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.